Implementasi Sosialisasi Stop Bullying dalam Meningkatkan Kesadaran Siswa Sekolah Dasar Berbasis Nilai Islam di Sekolah Dasar Negeri 15/1 Lubuk Ruso - Amaliani Eka Gusnika; Deriyan Safutra; Dian Arica; Dinda Aulia Delma; Hiqmah Putri Anugeraheni; M. Afif Fahrudin; Rida Juniyati; Rinaldi Puji Hasandy; Tegar Permana; Ibrohim; Fajri Al Mughni (Medan Resource Center, 2026)
Bullying in elementary school settings continues to pose a critical challenge that undermines students’ psychological well-being, social interaction, and academic development. This study examines how a stop bullying socialization program grounded in Islamic values is implemented and evaluates its effectiveness in enhancing students’ awareness at Sekolah Dasar Negeri 15/1 Lubuk Ruso, Pemayung District, Batang Hari Regency. Employing a descriptive qualitative design with an educative participatory approach, data were collected through observation, in-depth interviews, documentation, and interactive question-and-answer evaluations. The findings demonstrate that the program significantly improves students’ comprehension of bullying concepts, including its forms, adverse consequences, and prevention strategies. The integration of Islamic values such as compassion, justice, and brotherhood strengthens students’ moral reasoning and fosters empathetic, non-violent attitudes in daily interactions. The study argues that value-based socialization initiatives not only increase cognitive awareness but also contribute to the formation of positive character and a safer school climate. This approach offers a contextually relevant and sustainable educational strategy for addressing bullying in primary education environments.